Posterior uterine rupture secondary to use of herbs leading to peritonitis and maternal death in a primigravida following vaginal delivery of a live baby in western Uganda: a case report - Jonathan Peter Nelson (The Pan African Medical Journal, 2016)

(untitled)
Uterine rupture is a potentially avoidable complication resulting in poor perinatal and maternal outcomes. This case had a number of unusual features including delivery of a healthy live baby; spontaneous posterior uterine rupture in a primigravida (and unscarred uterus); and delayed presentation with signs of peritonitis and sepsis rather than haemorrhage. A 19-year old primigravida had a vaginal delivery of a live infant at term, reporting having taken herbs to induce labour. She deteriorated and was transferred to our unit where she was found to have reduced consciousness, a distended abdomen and signs of sepsis. At laparotomy there was blood-stained ascites, signs of peritonitis and a posterior lower segment uterine rupture. A sub-total hysterectomy was performed but the patient's condition worsened resulting in maternal death 5 days post-operatively. This case highlights a number of differences in the presentation, management and outcomes of uterine rupture in resource-poor compared to resource-rich countries.